Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Septin-dependent invasive growth by the rice blast fungus Magnaporthe oryzae - Iris Eisermann; Nicholas J. Talbot (Journal of Plant Diseases and Protection, 2024)
Septin GTPases are morphogenetic proteins that are widely conserved in eukaryotic organisms fulfilling diverse roles in cell division, differentiation and development. In the filamentous fungal pathogen Magnaporthe oryzae , the causal agent of the devastating blast diseases of rice and wheat, septins have been shown to be essential for plant infection. The blast fungus elaborates a specialised infection structure called an appressorium with which it mechanically ruptures the plant cuticle. Septin aggregation and generation of a hetero-oligomeric ring structure at the base of the infection cell is indispensable for plant infection. Furthermore, once the fungus enters host tissue it develops another infection structure, the transpressorium, enabling it to move between living host plant cells, which also requires septins for its function. Specific inhibition of septin aggregation—either genetically or with chemical inhibitors—prevents plant infection. Significantly, by screening for inhibitors of septin aggregation, broad spectrum anti-fungal compounds have been identified that prevent rice blast and a number of other cereal diseases in field trials. We review the recent advances in our understanding of septin biology and their potential as targets for crop disease control.

Filamentous pathogen effectors enter plant cells via endocytosis - Haixia Wang; Ely Oliveira-Garcia; Petra C. Boevink; Nicholas J. Talbot; Paul R.J. Birch; Barbara Valent (Trends in Plant Science, 2023)

Breaking the biotrophic interfacial complex: How genome editing can lead to rice blast resistance - Vincent Were; Nicholas J. Talbot (Molecular Plant, 2023)

Metabolic efficiency reshapes the seminal relationship between pathogen growth rate and virulence - Richard J. Lindsay; Philippa J. Holder; Nicholas J. Talbot; Ivana Gudelj (Ecology Letters, 2023)
A cornerstone of classical virulence evolution theories is the assumption that pathogen growth rate is positively correlated with virulence, the amount of damage pathogens inflict on their hosts. Such theories are key for incorporating evolutionary principles into sustainable disease management strategies. Yet, empirical evidence raises doubts over this central assumption underpinning classical theories, thus undermining their generality and predictive power. In this paper, we identify a key component missing from current theories which redefines the growth–virulence relationship in a way that is consistent with data. By modifying the activity of a single metabolic gene, we engineered strains of Magnaporthe oryzae with different nutrient acquisition and growth rates. We conducted in planta infection studies and uncovered an unexpected non‐monotonic relationship between growth rate and virulence that is jointly shaped by how growth rate and metabolic efficiency interact. This novel mechanistic framework paves the way for a much‐needed new suite of virulence evolution theories.

Number of COVID-19 cases required in a population to detect SARS-CoV-2 RNA in wastewater in the province of Alberta, Canada: Sensitivity assessment - Qiaozhi Li; Bonita E. Lee; Tiejun Gao; Yuanyuan Qiu; Erik Ellehoj; Jiaao Yu; Mathew Diggle; Graham Tipples; Rasha Maal-Bared; Deena Hinshaw; Christopher Sikora; Nicholas J. Ashbolt; et al. (Journal of Environmental Sciences, 2023)

The contribution of commercial fireworks to both local and personal air quality in Auckland, New Zealand - Joel D. Rindelaub; Perry K. Davy; Nicholas Talbot; Woodrow Pattinson; Gordon M. Miskelly (Environmental Science and Pollution Research, 2021)

The cyclin dependent kinase subunit Cks1 is required for infection‐associated development of the rice blast fungus Magnaporthe oryzae - Xiaofeng Yue; Yawei Que; Shuzhen Deng; Lin Xu; Miriam Oses‐Ruiz; Nicholas J. Talbot; Youliang Peng; Zhengyi Wang (Environmental Microbiology, 2017)
Summary Cell cycle regulation is pivotal for proper cell division and cellular differentiation in eukaryotic cells. The central regulators that govern eukaryotic cell cycle progression are cyclin‐dependent kinases (CDKs) and their partners. Here, we report that Magnaporthe oryzae CKS1 encodes a cyclin‐dependent kinase subunit, which plays a significant role in regulation of plant infection. We demonstrate that CKS1 is a functional homolog of CKS1 / SUC1 and can physically interact with the CDK protein Cdc28, and Som1, a downstream regulator of the cyclic AMP‐dependent Protein Kinase A pathway. CKS1 deletion mutants are severely impaired in hyphal growth, sexual reproduction, melanin pigmentation and conidiogenesis. Cks1 mutants are able to form appressoria from hyphal tips, but these are unable to re‐polarize, and rice infection is impaired. CKS1 also affects chitin and glucan synthase activity during cell wall differentiation and fungal hydrophobin function. CKS1 , therefore, encodes a conserved CDK‐binding partner, essential for appressorium‐mediated plant infection by the rice blast fungus.

The role of glycerol in the pathogenic lifestyle of the rice blast fungus Magnaporthe oryzae - Andrew J. Foster; Lauren S. Ryder; Michael J. Kershaw; Nicholas J. Talbot (Environmental Microbiology, 2017)
Summary The rice blast fungus Magnaporthe oryzae elaborates a specialized cell called an appressorium, which is used to breach the tough outer cuticle of a rice leaf, enabling the fungus entry to host plant cells. The appressorium generates enormous turgor by accumulating glycerol to very high concentrations within the cell. Glycerol accumulation and melanization of the appressorium cell wall collectively drive turgor‐mediated penetration of the rice leaf. In this review, we discuss the potential metabolic sources of glycerol in the rice blast fungus and how appressorium turgor is focused as physical force at the base of the infection cell, leading to the formation of a rigid penetration peg. We review recent studies of M. oryzae and other relevant appressorium‐forming fungi which shed light on how glycerol is synthesized and how appressorium turgor is regulated. Finally, we provide some questions to guide avenues of future research that will be important in fully understanding the role of glycerol in rice blast disease.

Corneal microprojections in coleoid cephalopods - Christopher Talbot; Thomas M. Jordan; Nicholas W. Roberts; Shaun P. Collin; N. Justin Marshall; Shelby E. Temple (Journal of Comparative Physiology A, 2012)

Separating the direct effect of hypoxia from the indirect effect of changes in cardiac output on the maximum pressure difference across the tricuspid valve in healthy humans - George M. Balanos; Nicholas P. Talbot; Peter A. Robbins; Keith L. Dorrington (Pflügers Archiv - European Journal of Physiology, 2005)

The vacuole as central element of the lytic system and sink for lipid droplets in maturing appressoria ofMagnaporthe grisea - Roland W. S. Weber; Gavin E. Wakley; Eckhard Thines; Nicholas J. Talbot (Protoplasma, 2001)